(untitled) (Computer systems and information technologies, 2023)
In the event of an emergency, there are still actions that people must take to save themselves. Currently, everyone has a mobile phone. Almost all establishments have an open Wi-Fi network. A model of the system that, when connected to the network, informs about the threats that have arisen and the actions that citizens must take to avoid damage. The alert system works around the clock. It complements the existing fire alarm and security systems. In the course of the work, an analysis of the existing models of cybersecurity threats for warning systems in emergencies was carried out, which showed that the requirements for the civil protection warning system currently need to be modernized. Therefore, the purpose of the work is to design and develop an extended cybersecurity threat model. The key aspects of the cybersecurity threat model are identified. A model of an intruder of such a warning system is presented. An extended cybersecurity threat model has been built using the Cyber Kill Chain.